2012
DOI: 10.1016/j.gaceta.2011.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Quality of pharmaceutical advertising and gender bias in medical journals (1998-2008): a review of the scientific literature

Abstract: The use of bibliographic references increased between 1998 and 2008. However, representation of traditional male-female roles was similar in 1975 and 2005. Pharmaceutical advertisements may contribute to reinforcing the perception that certain diseases are associated with the most frequently portrayed sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Advertising in marketing campaigns can help to strengthen erroneously the perception that certain diseases are more frequent in one sex than another through greater representation of one of the two sexes. In addition, concern has been consistently expressed that pharmaceutical marketing contributes to the medicalisation of women's life processes ( 7 ).…”
Section: Gender Biasmentioning
confidence: 99%
“…Advertising in marketing campaigns can help to strengthen erroneously the perception that certain diseases are more frequent in one sex than another through greater representation of one of the two sexes. In addition, concern has been consistently expressed that pharmaceutical marketing contributes to the medicalisation of women's life processes ( 7 ).…”
Section: Gender Biasmentioning
confidence: 99%
“…Due to the increasing global and fragmented context in which they work, physicians are partially dependent on the flow of information conveyed through advertising, which acts as a socialising agent and transmits messages that contribute to the social construction of disease (47). Marketing strategies target the medical community and do not always offer neutral information in order to increase sales (4850).…”
Section: Aim and Methodologymentioning
confidence: 99%
“…Advertisements make claims with insufficient or no substantiation; rely predominantly on research sponsored by the manufacturer; fail to quantify serious risks and overemphasise benefits over risks . Increased awareness of these issues has pushed pharmaceutical companies and their advertisers to raise the standards, with an increase in the number of references accompanying many advertisements . However, the increased number of references has not necessarily raised the quality of the claims in advertisements as many claims remain ambiguous, emotive, immeasurable and relate to non‐clinical outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…[2] Increased awareness of these issues has pushed pharmaceutical companies and their advertisers to raise the standards, with an increase in the number of references accompanying many advertisements. [3] However, the increased number of references has not necessarily raised the quality of the claims in advertisements as many claims remain ambiguous, emotive, immeasurable and relate to non-clinical outcomes. [4] In addition, some have found that the accompanying references do not support the claims made in some advertisements.…”
Section: Introductionmentioning
confidence: 99%